Tsunami Risk Analysis with Run-up Variation Scenario Based on Modeling of Geographic Information System on Sibolga City North Sumatera - Ridha Syafii Damanik, Muhammad; Nurman, Ali; Restu, R; Berutu, Nurmala; ., . (International Journal of Engineering and Technology, 2018)
This study aims to analyse the tsunami risk level based on scenarios of tsunami run-up variation in the coastline of Sibolga City. The input data on the model are a surface roughness map obtained from quick bird satellite imagery interpretation, slope map obtained from Indonesian Earth Map and run-up variation scenario with height 5, 10, 15, 20, and 25 meters. Tsunami risk level modelling was prepared using inundation height variables and land use vulnerability. The relationship between run-up height and tsunami risk level was analysed using simple linear regression. The total area of inundation was obtained based on the order of run-up variation by 1,35 km2, 1,92 km2, 2,47 km2, 3,27 km2, and 4,15 km2 while the area of high-risk category based on the order of run-up variation by 0,41 km2, 0,77 km2, 1,08 km2, 1,46 km2, and 1,95 km2. The result of linear regression between the run-up height and the width of the inundation area showed a positive correlation. Each 1-meter elevation of run-up will expand the inundation area by 0,14 km2. High run-up variables with high-risk areas also have a positive correlation. Each 1-meter of run-up will expand high-risk area at 0,75 km2.Â Â